Study of the Effect of TiO2 Layer on the Adsorption and Photocatalytic Activity of TiO2-MoS2 Heterostructures under Visible-Infrared Light. (20th January 2020) - Cruz-González, N.; Calzadilla, O.; Roque, J.; Chalé-Lara, F.; Olarte, J. K.; Meléndez-Lira, M.; Zapta-Torres, M.
Abstract : In the last decade, the urgent need to environmental protection has promoted the development of new materials with potential applications to remediate air and polluted water. In this work, the effect of the TiO2 thin layer over MoS2 material in photocatalytic activity is reported. We prepared different heterostructures, using a combination of electrospinning, solvothermal, and spin-coating techniques. The properties of the samples were analyzed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray diffraction (XRD), nitrogen adsorption-desorption isotherms, UV-Vis diffuse reflectance spectroscopy (UV-Vis-DRS), and X-ray photoelectron spectroscopy (XPS). The adsorption and photocatalytic activity were evaluated by discoloration of rhodamine B solution. The TiO2 -MoS2 /TiO2 heterostructure presented three optical absorption edges at 1.3 eV, 2.28 eV, and 3.23 eV. The high adsorption capacity of MoS2 was eliminated with the addition of TiO2 thin film. The samples show high photocatalytic activity in the visible-IR light spectrum.